Tailored antireflective biomimetic nanostructures for UV applications - Morhard, Christoph; Pacholski, Claudia; Lehr, Dennis; Brunner, Robert; Helgert, Michael; Sundermann, Michael; Spatz, Joachim P. (Nanotechnology, 2010)
Antireflective surfaces composed of biomimetic sub-wavelength structures that employ the ‘moth eye principle’ for reflectance reduction are highly desirable in many optical applications such as solar cells, photodetectors and laser optics. We report an efficient approach for the fabrication of antireflective surfaces based on a two-step process consisting of gold nanoparticle mask generation by micellar block copolymer nanolithography and a multi-step reactive ion etching process. Depending on the RIE process parameters nanostructured surfaces with tailored antireflective properties can easily be fabricated that show optimum performance for specific applications.
Gesehen am 04.05.2023